THE IPOB QUESTION: SEPARATIST AGITATION AND STATE REPRESSION IN SOUTHEAST NIGERIA - Njoku, Ekeledirichukwu (African Journal of Social and Behavioural Sciences, 2025)
This paper interrogates the Nigerian state’s heavy-handed approach towards the Indigenous People of Biafra (IPOB), a predominantly nonviolent separatist movement in the South-East. Despite IPOB’s pacifist tactics, which include rallies and diplomatic advocacy, the state has deployed disproportionate repression such as arbitrary arrests, military raids, and extrajudicial killings. Under the guise of counter-terrorism, security operations have ravaged communities, destroying properties and claiming civilian lives, including perceived IPOB sympathisers. Analysing secondary data through the lens of national security theory, this study reveals how the state’s securitised response stems from three factors: The South-East’s economic significance (particularly its oil reserves), historical anxieties rooted in the Biafra war legacy, and IPOB’s effective mobilisation of collective grievances. Far from quelling dissent, the state’s repression has amplified the separatist movement, exposing the folly of militarised solutions to political discontent. The paper argues that Nigeria’s refusal to engage accommodationist strategies such as dialogue, constitutional reforms, or fiscal federalism has only entrenched mistrust and exacerbated grievances. As IPOB’s support grows despite state crackdowns, the study underscores the urgency of a multifaceted approach in addressing structural inequities, revisiting the 2017 proscription, and prioritising justice for victims of security excesses.